2018
DOI: 10.1111/myc.12851
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of isavuconazole after posaconazole toxicity in leukaemia patients

Abstract: Isavuconazole was well-tolerated in patients discontinuing PCZ due to toxicity, with no patient discontinuing ISA due to toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 17 publications
(30 reference statements)
2
20
0
2
Order By: Relevance
“…Some studies indicated that the incidences of LFT abnormalities are generally transient and reversible for long-term posaconazole use [2,108,109]. Most studies found no correlation between posaconazole exposure and hepatotoxicity occurrence [107,[110][111][112]. Nevertheless, in 343 hematological patients receiving delayed-release tablets or intravenous injections, a posaconazole concentration of > 1.83 mg/L was proven to be correlated with grade 3/4 hepatotoxicity using classification and regression-tree analysis, although no association was found using logistic regression [113].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…Some studies indicated that the incidences of LFT abnormalities are generally transient and reversible for long-term posaconazole use [2,108,109]. Most studies found no correlation between posaconazole exposure and hepatotoxicity occurrence [107,[110][111][112]. Nevertheless, in 343 hematological patients receiving delayed-release tablets or intravenous injections, a posaconazole concentration of > 1.83 mg/L was proven to be correlated with grade 3/4 hepatotoxicity using classification and regression-tree analysis, although no association was found using logistic regression [113].…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…It is currently approved for the treatment of invasive aspergillosis and mucormycosis [4][5][6]. Today, there are limited real-life data on isavuconazole use as primary and secondary prophylaxis and treatment of invasive mold infections (IMI) in hematological patients and allogeneic hematopoietic cell transplant (HCT) recipients [7][8][9][10][11][12][13][14]. Although the existing data suggest a good tolerability and safety profile, a variable rate of breakthrough IMI, ranging from 3 to 18%, has been observed [7,11,12,14].…”
Section: Introductionmentioning
confidence: 99%
“…This trial offers strong evidence that isavuconazole is an appropriate alternative to voriconazole for first‐line treatment of invasive aspergillosis and other mold disease (AI). In addition, in patients who do not tolerate posaconazole due to toxicity, isavuconazole was found to be a safe alternative 35 …”
Section: Resultsmentioning
confidence: 99%